2009
DOI: 10.1111/j.1365-2095.2008.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary organic or inorganic selenium in rainbow trout (Oncorhynchus mykiss) under crowding conditions

Abstract: In the present study, the effects of different sources of selenium (Se; sodium selenite or selenomethionine) supplementation on the growth and serum concentrations of oxidative stress markers [malondialdehyde (MDA), 8‐isoprostane, glutathione peroxidase (GSH‐Px) activity] and muscle Se, MDA and heat shock protein 70 (Hsp70) levels in rainbow trouts were evaluated. The fish (n = 360; 0 +  years old) with initial average weight of 20 ± 0.8 g were randomly assigned to 12 treatment groups consisting of 3 replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 29 publications
9
60
3
1
Order By: Relevance
“…Therefore, it would be interesting to study the possible restoration of Se content by returning fish to a 'finishing' diet containing higher levels of FM and FO for a period of time before harvest, as has been shown for n-3 LC-PUFA (50)(51)(52) . Alternatively, the supplementation of aquafeeds with organic sources of Se (Se-enriched yeast), less likely to cause toxicity than inorganic sources, could be used as a measure to maintain adequate Se levels in salmon flesh, as shown for several other fish species (53)(54)(55)(56) . In addition, the use of processed animal proteins such as poultry by-product meal with an average Se content of approximately 0·78 mg/kg (57) could supply Se of high digestibility for aquafeeds.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be interesting to study the possible restoration of Se content by returning fish to a 'finishing' diet containing higher levels of FM and FO for a period of time before harvest, as has been shown for n-3 LC-PUFA (50)(51)(52) . Alternatively, the supplementation of aquafeeds with organic sources of Se (Se-enriched yeast), less likely to cause toxicity than inorganic sources, could be used as a measure to maintain adequate Se levels in salmon flesh, as shown for several other fish species (53)(54)(55)(56) . In addition, the use of processed animal proteins such as poultry by-product meal with an average Se content of approximately 0·78 mg/kg (57) could supply Se of high digestibility for aquafeeds.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of Hsp70 was quantified according to the procedure of Küçükbay et al, (2009) and the analysis of phosphorylation of AMP-activated protein kinase (p-AMPK) was essentially as described by (Shen et al, 2008). A frozen muscle sample (0.5 g) was homogenized using a polytron homogenizer in 5 mL buffer [for Hsp70: 10mM Tris-HCl (pH 7.4), 0.1mM NaCl, 0.1mM phenylmethylsulphonyl fluoride (PMSF), 5μM soybean (soluble powder; Sigma, St. Louis, MO, USA) as trypsin inhibitor; for p-AMPK, 20mM Tris-HCl (pH 7.4 at 4°C), 2% SDS, 5mM EDTA, 5mM EGTA, 1mM DTT, 100mM NaF, 2mM sodium vanadate, 0.5mM PMSF, 10 μg/ml leupeptin, and 10 μg/ml pepstatin].…”
Section: Immunoblotting Analysis For Hsp70 and Phosphorylation Of Ampmentioning
confidence: 99%
“…14 Se supplementation of fish feeds has been already investigated in several studies, 15−17 but criteria taken into consideration to evaluate the effects of such supplementation on Se metabolism differ depending on studies. Schram et al 17 determined total Se and Se speciation in muscle, Kucukbay et al 15 measured total Se in both muscle and serum, as well as GPx activity in serum, and Rider et al 16 quantified total Se in whole body of fish and also determined hepatic GPx and TRx activities. The two latter studies concluded on a beneficial effect of Se supplementation and on the superiority of the organic form of Se supplementation over supplementation with selenite.…”
Section: ■ Introductionmentioning
confidence: 99%